Investigation of O3‐Al2O3/H2O‐Al2O3 dielectric bilayer deposited by atomic‐layer deposition for GaN MOS capacitors. Issue 10 (20th May 2016) - Shen, Zhen; He, Liang; Zhou, Guilin; Yao, Yao; Yang, Fan; Ni, Yiqiang; Zheng, Yue; Zhou, Deqiu; Ao, Jinping; Zhang, Baijun; Liu, Yang
Abstract : In this work, H2 O‐Al2 O3 /O3 ‐Al2 O3 insulating bilayers were grown on GaN by atomic‐layer deposition (ALD) technique using H2 O vapor and O3 as oxidants. The electrical and material properties show that the H2 O‐Al2 O3 /O3 ‐Al2 O3 stack structure appeared to be an appropriate dielectric for GaN MOS devices that had low leakage current densities, high breakdown voltages, and good capacitance–voltage ( C–V ) curves. The H2 O‐Al2 O3 interlayer between the O3 ‐Al2 O3 and GaN efficiently prevented the GaN surface from oxidizing by ozone oxidant by its strong oxidizing power. By taking photo‐assisted C–V measurements, it was found that the deep interface state densities at the Al2 O3 /GaN interface reduced, while increasing the thicknesses of the H2 O‐Al2 O3 interlayer restricted the "V th shift" phenomenon and improved the stability and reliability of the GaN MOS devices.